Evaluation of the antimicrobial properties of natural extracts of Ganoderma lucidum - Abarca-Cascante, Karina (2024)
There is a growing importance of alternative anticancer and anti-inflammatory treatments. Current interest lies in natural medicine and secondary metabolites present in plants, particularly focusing on triterpenes. Ganoderma lucidum is a fungal species of significant commercial interest due to its therapeutic and medicinal properties resulting from secondary metabolites such as polysaccharides and triterpenes. These compounds exhibit antitumor activity and bolster the immune system. The study aimed to assess the antimicrobial activity of G. lucidumextracts, both commercial and wild. The content of ganoderic acids in all extracts showed a slight difference in concentration between commercial and wild extracts. However, no bacterial inhibition halos were observed in any of the strains used. The presence of varying concentrations of ganoderic acids among treatments underscores the importance of optimizing and standardizing a comprehensive strategy for extracting secondary metabolites, focusing on producing high-quality supplements and pharmaceutical products. Furthermore, preserving the stability of the obtained triterpenes is necessary due to their importance in the medicinal properties of the fungus.